2018
DOI: 10.1002/rra.3379
|View full text |Cite
|
Sign up to set email alerts
|

Historical and predicted variations of baseflow in China's Poyang Lake catchment

Abstract: Baseflow availability and its contribution to streamflow are critical for planning and management of catchment hydrology and ecology. This study uses a digital filtering technique, statistical methods, and hydrological projection to investigate historical and future baseflow characteristics with respect to climate and land use impacts, exemplified by the large Poyang Lake catchment (China). Digital filtering results show that annual baseflow varied between 25 × 108 and 820 × 108 m3/year for the catchment river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Baseflow has been identified as the water that maintains streamflow during low-flow periods and also the components in high-flow periods, which consist mainly of groundwater or other sources [1][2][3] or the streamflow components that respond slowly to precipitation and are associated with groundwater discharge [4][5][6]. Many recent studies have identified baseflow as the flow resulting from groundwater discharge, which is mainly composed of shallow, lateral, and deep groundwater and other delayed sources, such as lakes, wetlands, and reservoir storage [7][8][9][10][11], and changes gradually in the short-and long-terms [12,13]. Baseflow is not only a key source of basic streamflow but also plays an important role in groundwater systems [6,7,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseflow has been identified as the water that maintains streamflow during low-flow periods and also the components in high-flow periods, which consist mainly of groundwater or other sources [1][2][3] or the streamflow components that respond slowly to precipitation and are associated with groundwater discharge [4][5][6]. Many recent studies have identified baseflow as the flow resulting from groundwater discharge, which is mainly composed of shallow, lateral, and deep groundwater and other delayed sources, such as lakes, wetlands, and reservoir storage [7][8][9][10][11], and changes gradually in the short-and long-terms [12,13]. Baseflow is not only a key source of basic streamflow but also plays an important role in groundwater systems [6,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have identified baseflow as the flow resulting from groundwater discharge, which is mainly composed of shallow, lateral, and deep groundwater and other delayed sources, such as lakes, wetlands, and reservoir storage [7][8][9][10][11], and changes gradually in the short-and long-terms [12,13]. Baseflow is not only a key source of basic streamflow but also plays an important role in groundwater systems [6,7,14]. In the dry season, most streamflow consists of baseflow, whereas in the wet season, precipitation is the main source of streamflow, and the proportion of baseflow is low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies adopted graphical, analytical, and digital filtering techniques to partition the baseflow from the total streamflow. In general, digital filtering methods can remove inconsistencies inherent in graphical methods and reduce the time required for hydrograph separation [ 16 ]. Additionally, filtering methods do not have a hydrological basis but aim to generate an objective, repeatable, and easily automated method to obtain baseflow dynamics of a catchment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baseflow in mountainous regions has been studied extensively because of shifts in snowmelt timing that may cause baseflow discharge earlier in the year (e.g., Barnett et al ., 2005; Stewart et al ., 2005; Huntington and Niswonger, 2012). Other studies have analysed the impact of projected climate change on baseflow, but in other parts of the world (e.g., Eckhardt and Ulbrich, 2003; Nyenje and Batelaan, 2009; Samuel et al ., 2012; Hellwig and Stahl, 2018; Kahsay et al ., 2018; Li and Zhang, 2018; Peterson et al ., 2020) or on a larger, global scale (e.g., Koirala et al ., 2014). Because statistical models are less computationally intensive and are easier to implement over large regions, they can help fill in the gap to project changes in baseflow.…”
Section: Introductionmentioning
confidence: 99%